2021
DOI: 10.3390/jcm10132873
|View full text |Cite
|
Sign up to set email alerts
|

Association between Oral Hygiene and Metabolic Syndrome: A Systematic Review and Meta-Analysis

Abstract: Emerging evidence has linked poor oral hygiene to metabolic syndrome (MetS), but previously, no summary of evidence has been conducted on the topic. This systematic review and meta-analysis aims to evaluate the associations of oral hygiene status and care with MetS. A systematic search of the PubMed and Web of Science databases from inception to March 17, 2021, and examination of reference lists was conducted to identify eligible observational studies. A random-effects model was applied to pool the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The included studies were then divided into three categories: high (>7 points), moderate (4-6 points), and poor (0-3 points) in terms of overall quality scores. 8 Any dispute between the two reviewers about the quality of methodology and evidence score of the included articles was adjudicated by DQT.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…The included studies were then divided into three categories: high (>7 points), moderate (4-6 points), and poor (0-3 points) in terms of overall quality scores. 8 Any dispute between the two reviewers about the quality of methodology and evidence score of the included articles was adjudicated by DQT.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Our finding that oral health behavior correlated with the daily intake of vitamins must be useful for health guidance in multidisciplinary healthcare. A recent meta-analysis revealed that good oral hygiene status, frequent tooth brushing, and frequent interdental cleaning were associated with a lower risk of metabolic syndrome [ 53 ]. Oral frailty may precede systemic frailty, and older adults with frailty often exhibit poor oral hygiene status and inadequate oral health behavior [ 54 ].…”
Section: Discussionmentioning
confidence: 99%